2020
DOI: 10.29228/turkishstudies.39933
|View full text |Cite
|
Sign up to set email alerts
|

Sınıf Öğretmenlerinin Üstün Yetenekli Öğrencilerin Eğitimine Yönelik Tutum, Öz-Yeterlik ve Eğitim İhtiyaçlarının Belirlenmesi

Abstract: Primary school teachers have a great role in the education of gifted students. Attitudes and selfefficacy beliefs of primary school teachers towards the education of gifted students play a key role in this task. Therefore, the aim of this study was to determine the attitudes, self-efficacy beliefs and educational needs of primary school teachers regarding the education of gifted students. The research was carried out with 100 primary school teachers working in various provinces in the fall semester of 2019-202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…In the study, it was observed that the self-efficacy of classroom teachers regarding the education of gifted students did not differ in terms of professional seniority. Yıldız (2020) found no difference in classroom teachers' self-efficacy beliefs towards gifted education in terms of professional seniority. Abanoz (2021) concluded that teachers between the ages of 20-29 were more conscious about the education of gifted students than teachers aged 50 and over.…”
Section: Conclusion and Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In the study, it was observed that the self-efficacy of classroom teachers regarding the education of gifted students did not differ in terms of professional seniority. Yıldız (2020) found no difference in classroom teachers' self-efficacy beliefs towards gifted education in terms of professional seniority. Abanoz (2021) concluded that teachers between the ages of 20-29 were more conscious about the education of gifted students than teachers aged 50 and over.…”
Section: Conclusion and Discussionmentioning
confidence: 60%
“…In this study, when the self-efficacy of classroom teachers regarding the education of gifted students was examined in terms of gender, it was concluded that there was a differentiation in favour of men in the personality trait subdimension. When the literature was examined, it was found that different results were reached and that there was no significant difference between the attitudes and self-efficacy of classroom teachers towards gifted students and the gender variable (Güneş, 2015;Dinçer, 2019), as well as research findings (Girgin & Şahin, 2019;Vatansever Bayraktar, Kadıoğlu Ateş & Afat 2019;Yıldız, 2020) showing that male teachers' self-efficacy for the education of gifted students is higher than female teachers. In another study, it was concluded that women's self-efficacy levels in Mentoring and Responsibility dimensions were statistically significantly higher than men (Abanoz, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%